Catholic Church, Lagos, Nigeria, ca.1917 (IMP-YDS-RG101-016-0000-0020) - Auteur inconnu (Wikimedia Commons, 1917)
Carte postale ancienne issue de Wikimedia Commons. Titre: Catholic Church, Lagos, Nigeria, ca.1917 (IMP-YDS-RG101-016-0000-0020). Catholic Church, Lagos, Nigeria, ca.1917 "15. Lagos - After Sunday's service catholic Church" Several African people in Western-style dress are walking on a path in front of a large brick or stone church. | The back of the postcard has a handwritten message in French and is postmarked 1917. Subject (aat): general views Photographer: Unidentified Filename: IMP-YDS-RG101-016-0000-0020 Coverage date: 1917 Subject (unesco): Churches | Indigenous populations Part of collection: International Mission Photography Archive, ca.1860-ca.1960 Type: images Part of subcollection: Photographs from the Yale Divinity School Library, New Haven, Connecticut, ca.1880-1950 Repository name: Yale University. Divinity School. Day Missions Library Archival file: impa_Volume313/IMP-YDS-RG101-016-0000-0020-0.tiff Previous format (aacr2): photographic postcards, 9 x 14 cm. Repository address: Yale University Divinity School Library, 409 Prospect Street, New Haven, CT 06511 Geographic subject (country): Nigeria Geographic subject (continent): Africa Rights: Yale University. Divinity School. Day Missions Library Part of series: Yale Divinity Library Special Collections | Missionary Postcard Collection Repository email: Divinity.Library@yale.edu Date created: 1917 Publisher (of the digital version): University of Southern California. Libraries Format (aat): photographs Legacy record ID: impa-m69261 Access conditions: http://www.library.yale.edu/div/reproductions.html File: YDS/RG101/016/0000/0020
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; église; Carte postale